Slang Created and Used in 1Cak.com Site: A Sociolinguistics Study - Harared, Nico (Bina Nusantara University, 2018)
This research investigated the slang created based on word formation processes as well as a its functions, and to describe the social factors influencing the existence of slang. The form of this research was qualitative method which resulted in descriptive data. The data were collected by using observations method (screenshot) on the meme or posts which follow certain postings of pictures. Then, it was followed by full observation method for there to be no interference from the researcher on the data collected. The data were taken from ‘trending’ and ‘legend’ posts in 1cak.com site. The focus of the research was on the analysis of slang by describing its word formation processes and functions. In this research, first, it is found that some of the types of slang words formation processes according to Yule are used in 1cak.com. They are clipping, blending, borrowing, acronyms, initials, and derivation by adding with specific affixes (suffix). Second, it is found that there are two additional functions of slang language to add to what Coleman has proposed; that there are 26 reasons why people use slang, such as mocking and praising. The social factors proposed by Johnstone & Marcellino in Speaking Hymes theory also influence the appearance and existence of slang. Social factors and situational factors that influence the use of language cause variations in language.